MIDNIGHT LIBRARY - MATT HAIG (EDINBURGH CANONGATE, 2020)
When we are fast asleep in bed, the midnight library opens its doors to all the night-time animals. Inside the library the little librarian and her three assistant owls help each and every animal to find the perfect book. But with a noisy squirrel band, an upset wolf and a slow-reading tortoise to help, they could all be in for a very busy night.
Keywords: ENGLISH - NOVEL